2020
DOI: 10.1186/s13006-020-00276-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of prenatal food insecurity on breastfeeding behaviors: findings from the United States pregnancy risk assessment monitoring system

Abstract: Background: In addition to its health and nutritional benefits, breastfeeding can save low-income, food insecure mothers the cost of infant formula so that money can be spent on food and other necessities. Yet breastfeeding may exacerbate food insecurity by negatively affecting maternal employment. The relationship between food insecurity and breastfeeding has been explored previously, with varying results. The purpose of this study was to determine the relationship between prenatal food insecurity and breastf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
(65 reference statements)
3
17
0
Order By: Relevance
“…In Brazil, a higher prevalence of BF has been found among food-insecure families of children aged 12-24 months (Gomes & Goubert, 2012). However, this result has not been observed in developed countries where inverse or no associations between food insecurity and breastfeeding initiation and duration were reported (Dinour et al, 2020;Orr et al, 2018). Similar to previous findings (Pacheco et al, 2021), no association of BF patterns with COVID-19 related exposure was found.…”
Section: Discussionsupporting
confidence: 65%
“…In Brazil, a higher prevalence of BF has been found among food-insecure families of children aged 12-24 months (Gomes & Goubert, 2012). However, this result has not been observed in developed countries where inverse or no associations between food insecurity and breastfeeding initiation and duration were reported (Dinour et al, 2020;Orr et al, 2018). Similar to previous findings (Pacheco et al, 2021), no association of BF patterns with COVID-19 related exposure was found.…”
Section: Discussionsupporting
confidence: 65%
“…In response to the COVID-19 pandemic, South Africa imposed a strict national lockdown on 27 March 2020, which resulted in severe job and income losses, as well as food insecurity and mental health concerns [ 5 ]. This study was inspired by this context and the literature on lower breastfeeding rates and earlier cessation of exclusive breastfeeding seen with increased severity of food insecurity experienced by the mother and the household [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the broader population, skipping meals may not always be a choice as approximately 10% of pregnant people experience prenatal food insecurity, 30 whereas, in this sample the majority of participants reported regularly eating all three meals during the control period. The prevalence of skipping a meal during the week and the 24 hours before labor onset was greater among non‐Hispanic Black participants.…”
Section: Discussionmentioning
confidence: 72%